Ultrasonic study of homœopathic solutions - Silvio, Maranta; Arnaldo, Paparelli (British Homeopathic Journal, 1990)
Ultrasonic velocity and absorption measurements have been performed in homœopathic solutions and in corresponding placebo solutions. The possibility of microstructural differences between ‘normal water’ and ‘homœopathic’ water solutions was investigated by propagation of ultrasonic waves in diluted water-ethanol mixtures. Our spectroscopic results do not display any difference between the two liquid systems.
Keywords: Physical properties; Ultrasonic; Water; Dynamization